Establishment, optimization, and application of genetic technology in Aspergillus spp. - Gao, Jing; Liu, Huiqing; Zhang, Zhenzhen; Liang, Zhihong (Frontiers in Microbiology, 2023)
Aspergillus is widely distributed in nature and occupies a crucial ecological niche, which may produce harmful mycotoxins causing serious contamination and threaten human health. But more notably, it could be a promising cell factory for medicine, agricultural, and food industries. With the deepening of genomics exploration, a series of genome editing technologies have been developed, which not only help us understand the basic mechanism of organisms, but also further realize the ideal functional transformation. Genetic engineering involves the transformation of artificially modified or synthetic nucleic acid fragments, the target editing of genes, and the screening of desirable trait transformants. Available tools include homologous recombinant systems, specific nuclease based systems, and RNA techniques, combined with transformation methods, and screening based on selective labeling. The challenges of gene editing technology can be optimized at multiple levels, including transcription, post-transcription, and translation. This paper reviews recent progress in genetic technology, analyzes the challenges and the possibility of future development with regard to Aspergillus.